2009
DOI: 10.1016/j.jpainsymman.2008.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Pain in Children and Adults with Cystic Fibrosis: A Comparative Study

Abstract: Pain is a potential complication of cystic fibrosis (CF), but its consequences in daily life and other issues of pain management are not yet clearly understood. We undertook a comparative study of children and adults with CF to assess the prevalence of pain symptoms, their characteristics and treatment, their impact on daily quality of life, and the occurrence of procedural pain. The study included 73 children (1-18 years) and 110 adults (18-52 years); 59% of the children and 89% of the adults reported at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
84
1
24

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(119 citation statements)
references
References 18 publications
10
84
1
24
Order By: Relevance
“…27 Our data on the number of cycles received were also similar to those from randomized controlled trials, 21,28 although patients older than 70 years contributed <10% of the population in these trials compared with 30% in our study. Our study is the first assessment of RDI in CRC patients receiving a homogeneous adjuvant chemotherapy regimen in the real-life setting.…”
Section: External Validitysupporting
confidence: 83%
“…27 Our data on the number of cycles received were also similar to those from randomized controlled trials, 21,28 although patients older than 70 years contributed <10% of the population in these trials compared with 30% in our study. Our study is the first assessment of RDI in CRC patients receiving a homogeneous adjuvant chemotherapy regimen in the real-life setting.…”
Section: External Validitysupporting
confidence: 83%
“…Our study showed in subgroup of patients with pain a link between the quality of sleep and the intensity of pain 34,35 , whose location was heterogeneous. As in the study conducted by Lechtzin et al 36 , the abdomen and head/sinuses were the sources of pain most often indicated by patients.…”
Section: Discussionmentioning
confidence: 63%
“…Pain characteristics did not differ according to age or gender in that study [5] conversely to the Perquin report [14] which found more prevalent chronic pain in females and in patients over 12 years of age. In a recent survey of pain in CF patients throughout their lives, Sermet-Gaudelus et al [6] outlined a high incidence of untreated pain; they studied 73 children and 59% reported at least one episode of pain during the previous month, with prevalent abdominal location (60%) and mean pain intensity on the FPS-R of 4.9; 15% reported school absenteeism and one-third of the cohort reported a negative impact on their family life. Contrary to the study done by Koh et al [5], the authors emphasised that CF children experienced intense, longlasting and recurrent pain episodes.…”
Section: Discussionmentioning
confidence: 99%
“…Cystic fibrosis (CF) children commonly experience abdominal pain whatever the severity of disease [5,6] but such studies must be interpreted with caution since patients were asked to report pain experienced over a period of time without longitudinal pain assessment; moreover gastrointestinal investigations aimed at assessing pain aetiology were missing. Thus, we conducted a prospective cross-sectional study using Apley's criteria to define recurrent abdominal pain (RAP): "at least three bouts of pain, severe enough to affect activities, over a period of not less than 3 months, with attacks in the year preceding the examination" [7].…”
Section: Introductionmentioning
confidence: 99%